Best performance of the UNB modulation VMSK in AWGN channel - YANG Dong-kai; WU Hua-sen; ZHANG Qi-shan (Tongxin xuebao)
VMSK （very minimum shift keying） was taken into account as UNB example. Its performance in AWGN （added white Gaussian noise） channel is analyzed based on the classifier model for signal processing. The detecting method with the lowest bit error rate is analyzed according to the Bayesian criterion using the basic probability method. Then the comparison with correlation detection,optimal performance is given. The analysis shows that the VMSK needs higher SNR （signal noise ratio） than BPSK to get the same BER performance. And the conclusion can be extended to other UNB modulation methods.